Clinical applications and novel approaches in stem cell: an insight to dental pulp regeneration - Syeda Abeerah Tanveer; Zainab Haji; Robia Ghafoor (Journal of the Pakistan Medical Association, 2023)
Objectives: The aim of the review is to present the currently applied tissue regeneration through stem cells technology in regenerative endodontics. This review also summarises the various preclinical models used for the evaluation of stem cell-based therapies, their limitations, recent advances and challenges related to clinical applications of human stem cells. Methodology: A literature survey from 2010 to August 2022 was carried out in various electronic databases to identify the articles required for review on Pulp Regeneration through Stem Cells Technology. MeSH terms/keywords such as “Pulp regeneration,” “Pulp Revascularization,” “Pulp revitalization,” “Regenerative Endodontics” were used to search in the electronic databases comprised of PubMed database, SCOPUS, COCHRANRE library, EMBASE, CINAHL, ICTRP, Science Direct and a manual search was also done using the cross references and textbooks. Results: The searches revealed 299 articles. After reading the full text articles and applying the inclusion and exclusion criteria 15 articles were selected for the review fulfilling the criteria of the study. Conclusion: Currently in regenerative endodontics, there is a broad consent that the final tissue acquired is more likely to bone-like tissue mixed with connective tissue rather than the pulp-dentin complex. Moreover, re-innervation from sensory axons in regenerated tissue, is still to date, difficult to achieve. Keywords: Endodontics, Biocompatible, Pulp, Stem Cells, Tissue, Dentin, Axons